2005
DOI: 10.1080/03079450500368334
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of duck circovirus infections by conventional and real-time polymerase chain reaction tests

Abstract: Development of the first conventional and real-time polymerase chain reaction (PCR) tests for the diagnoses of duck circovirus (DuCV) infections is described. Both tests amplified a 230 bp fragment specific to the DuCV Rep gene. Although both tests had the same detection limit (13 )/10 3 target DNA/ml) when the target DNA was diluted in water, the detection limit of the real-time test (13 )/10 4 target DNA/ml) was 10-fold less than the conventional test (13)/10 5 target DNA/ml) when the amplifications were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 10 publications
1
28
0
2
Order By: Relevance
“…The data indicated that PiCV load in sick young pigeons is particularly high in tissues such as the liver (ranging from 2.65)10 5 to 2.88)10 8 copies genome/mg), the spleen (6.88)10 5 to 5.57)10 8 copies genome/mg) and the BF (1.25 )10 6 to 2.07)10 9 copies genome/mg). High virus loads have also been detected by semiquantitative dot blot hybridization in BF tissues of pigeons (Todd et al, 2002), and similar results were recorded for duck circovirus infection by real-time PCR (Fringuelli et al, 2005). Although the numbers of birds investigated were small, a significant difference in the viral loads of liver was detected between YPS and apparently healthy infected pigeons.…”
Section: Discussionsupporting
confidence: 75%
“…The data indicated that PiCV load in sick young pigeons is particularly high in tissues such as the liver (ranging from 2.65)10 5 to 2.88)10 8 copies genome/mg), the spleen (6.88)10 5 to 5.57)10 8 copies genome/mg) and the BF (1.25 )10 6 to 2.07)10 9 copies genome/mg). High virus loads have also been detected by semiquantitative dot blot hybridization in BF tissues of pigeons (Todd et al, 2002), and similar results were recorded for duck circovirus infection by real-time PCR (Fringuelli et al, 2005). Although the numbers of birds investigated were small, a significant difference in the viral loads of liver was detected between YPS and apparently healthy infected pigeons.…”
Section: Discussionsupporting
confidence: 75%
“…Because of the absence of available cell culture for the isolation of DuCV, the PCR assays were often used for detecting DuCVs (Hattermann et al, 2003;Fringuelli et al, 2005;Jiang et al, 2008;Zhang et al, 2009;Wan et al, 2011;Wang et al, 2011). However, these methods cannot be used to distinguish mixed infection of DuCV-1 and DuCV-2.…”
Section: Discussionmentioning
confidence: 99%
“…There were multiple local lesions in the spleen, thymus and BF of ducks infected with DuCV (Liu et al, 2010b). Surveys would suggest a high prevalence of the virus in flocks experiencing morbidity and mortality as well as those that appear clinically normal (Fringuelli et al, 2005;Chen et al, 2006;Banda et al, 2007;Jiang et al, 2008;Zhang et al, 2009;Liu et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…PCR assays to detect duck circovirus (DuCV) in duck embryos and goose circovirus (GoCV) and goose haemorrhagic polyomavirus (GHPV) in samples from goose embryos were also conducted. The primers for detection of those viruses and PCR reaction parameters were described by Sellers et al (2004) for ARV, by Wozniakowski et al (2009) for DDV, by Plummer et al (1998) for DEV, by Fringuelli et al (2005) for DuCV, by Ball et al (2004) for GoCV and by Guerin et al (2000) for GHPV.…”
Section: Methodsmentioning
confidence: 99%